Taste of home one-dish meals. (Taste of Home Books, RDA Enthusiast Brands, LLC, 2025)
"From casseroles, protein bowls and slow-cooked favorites to sheet-pan suppers, entrée salads and Instant-Pot greats, the timesaving specialties in this all-new cookbook get dinner on the table fast. No need to plan menus or prepare separate sides with Taste of Home One-Dish Meals at your fingertips"--